Deciphering the regulatory role of ELF5 in buffalo lactation - Gao, Ruixia; Wang, Rongping; Huang, Lige; Fan, Xinyang; Qian, Lindong; Miao, Yongwang (Frontiers in Veterinary Science, 2025)
E74 Like ETS Transcription Factor 5 (ELF5) has been implicated in milk protein synthesis in various mammals, but its precise roles and mechanisms in buffalo have remained largely unknown. This study successfully isolated and characterized ELF5 from buffalo mammary gland tissues, revealing a 768 bp coding sequence (CDS) that translates into a 255 amino acid protein. Bioinformatics analysis identified a conserved ETS domain within ELF5, crucial for transcriptional regulation, along with several predicted post-translational modification sites, including phosphorylation, N-glycosylation, and N-myristoylation. Molecular docking analysis further showed that ELF5 probably interacts with the STAT5A protein through hydrogen bonds and salt bridges, and forms hydrogen bonds with STAT5B, suggesting potential regulatory interactions with STAT5A and STAT5B. Experimentally, ELF5 was localized to the nucleus and cytoplasm of buffalo mammary epithelial cells (BuMECs). Notably, ELF5 expression was highest in the buffalo mammary gland among the eight tissues and was significantly higher in lactating BuMECs than in non-lactating BuMECs. Functionally, in the BuMECs, overexpression of ELF5 significantly upregulated mRNA and protein levels associated with milk protein synthesis, increased casein concentrations, and enhanced BuMECs metabolic activity associated with proliferation. These effects were mediated through the JAK2-STAT5 and PI3K/AKT1/mTOR signaling pathways. Conversely, ELF5 knockdown led to the opposite effects. Collectively, these findings provide novel insights into the molecular mechanisms of ELF5-mediated regulation of milk protein synthesis in buffalo, highlighting its potential as a key factor in enhancing milk production.